Business Model Canvas : The ‘Bahulu’ Cake Machine / Nor Farhana Izwanie Anuar Zamani - Anuar Zamani, Nor Farhana Izwanie (2020)
All people can become successful entrepreneurs. By doing this ‘Bahulu’ Machine Cake, I’m targeting the small-medium entrepreneurs and housewives. For age range, I think it doesn’t matter because people nowadays become entrepreneurs since they are young. Firstly, my target is small-medium entrepreneurs who make a ‘bahulu’ cake as their business. Even though they do small business but they can make a lot of profit. People nowadays do not care about quality rather than quantity. They make a lot of money but the taste is unfavourable. With this machine, they can make a high profit because this machine is an innovative and they will get a traditional ‘bahulu’ cake. Secondly, a housewife is one of the customers that can buy my product. It is because if they bored at home, they can open a business by using this machine. And also they can make a lot of money and they can have fun by doing business.